2019
DOI: 10.1093/infdis/jiz168
|View full text |Cite
|
Sign up to set email alerts
|

Early Clearance of Mycobacterium tuberculosis: The INFECT Case Contact Cohort Study in Indonesia

Abstract: Background Early clearance of Mycobacterium tuberculosis is the eradication of infection before an adaptive immune response develops. We aimed to identify host factors associated with early clearance. Methods Indonesian household contacts patients with smear-positive tuberculosis (TB) had an interferon-γ release assay (IGRA) at baseline and 14 weeks later. Early clearance was defined as a persistently negative IGRA. Contact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 22 publications
3
64
0
1
Order By: Relevance
“…In so doing, trained AM will be able to overcome the innate immune tolerogenic/suppressive effects of M.tb upon exposure for enhanced innate protection. Indeed, it has been observed that up to 20% of the human house contacts exposed to M.tb could quickly clear infection (early clearers) as judged by lack of conversion in the interferon‐gamma‐release assay and purified protein derivative skin test, 55 and such protection is associated with increased innate immune responses and BCG vaccination 58,59 …”
Section: Innate Immune Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…In so doing, trained AM will be able to overcome the innate immune tolerogenic/suppressive effects of M.tb upon exposure for enhanced innate protection. Indeed, it has been observed that up to 20% of the human house contacts exposed to M.tb could quickly clear infection (early clearers) as judged by lack of conversion in the interferon‐gamma‐release assay and purified protein derivative skin test, 55 and such protection is associated with increased innate immune responses and BCG vaccination 58,59 …”
Section: Innate Immune Tolerancementioning
confidence: 99%
“…Interrogating the innate immune training effects at local mucosal tissue levels following parenteral BCG vaccination represents a timely quest. It will help understand the innate immune mechanisms underlying the early, adaptive immunity‐independent clearance of M.tb in the lung upon exposure observed among BCG‐vaccinated humans who were in close contact with index TB cases 55,58,59 . The circulating mononuclear cells from these early clearers produced enhanced proinflammatory cytokines in response to heterologous pathogens E. coli and S. pneumoniae .…”
Section: Bcg Vaccination and Tiimentioning
confidence: 99%
“…Third, in a recent study, Verrall et al 5 found that early clearance of M. tuberculosis is associated with increased innate immune responses. Likewise, the clearance of M. tuberculosis may be associated with T-cell responses.…”
Section: Dear Sirmentioning
confidence: 96%
“…As mentioned before, the study of the mechanisms underlying immunity to Mtb infection has focused on immunological memory mediated by adaptive immune cells, mainly CD4+ T helper lymphocytes. However, human studies have shown that up to a quarter of the individuals that are in close contact with active TB patients remain clear of the infection (16). These individuals test negatively in the purified protein derivative (PPD) skin test and IFN-γ release assays (IGRAs) (16,17), which are two indirect readouts of adaptive responses against immune-dominant Mtb antigens.…”
Section: Memory Responses Against Mtb Within the Innate Immune Systemmentioning
confidence: 99%
“…However, human studies have shown that up to a quarter of the individuals that are in close contact with active TB patients remain clear of the infection (16). These individuals test negatively in the purified protein derivative (PPD) skin test and IFN-γ release assays (IGRAs) (16,17), which are two indirect readouts of adaptive responses against immune-dominant Mtb antigens. A positive BCG vaccination history has been associated with this state of immune protection (16).…”
Section: Memory Responses Against Mtb Within the Innate Immune Systemmentioning
confidence: 99%